Political branding on X: sentiment dynamics in Indonesia’s presidential discourse - Sukendar, Markus Utomo; Susanto, Agus; Naidoo, Gedala Mulliah (Jurnal Studi Komunikasi, 2025)
This study investigated the strategic construction of political personal branding on social media within Indonesia’s dynamic political landscape, focusing on how it is manifested and contested through user-generated content about Prabowo Subianto on X (formerly Twitter). This study examined how visual symbols, hashtags, and popular culture references influence public opinion and reveal contrasting narratives that reflect the polarised nature of Indonesia’s digital public sphere. Employing a mixed-methods approach, algorithmic sentiment analysis (Naive Bayes) is combined with qualitative visual-symbolic coding. Findings reveal a dominant negative sentiment coexisting with strong pro-candidate messaging enriched by humour and affectionate visuals. This duality suggests potential audience segmentation and deliberate efforts to humanise the candidate, creating digital echo chambers for loyal supporters despite widespread criticism. The results highlight the strategic use of humour and emotional appeal by campaign teams and supporters to reconstruct public image, drawing on principles of affective engagement and participatory branding. The study provides valuable insights into how political figures and their communication strategies navigate polarised environments, offering key lessons for digital political public relations in an era shaped by emotion, culture, and interaction